Is the anomalous monism an ally of the anti-constructive naturalism? - Pogoda, Patryk (Hybris, 2013)
The paper argues that Davidson’s thesis of the anomalous character of mental life is a natural supporter for McGinn’s anti-constructive naturalism. In the first two parts of the article I discuss both positions. In the third I will try to show similarities and differences between them and the way in which anomalous monism can support McGinns theory.